TANGGUNG JAWAB PENGUSAHA TOKO FUN SHOP DALAM PEMBERIAN GARANSI TERHADAP PEMBELI PADA PERJANJIAN JUAL BELI LAPTOP DI KOTA PONTIANAK - - A11112140, TOMMY PRATAMA (Jurnal Hukum Prodi Ilmu Hukum Fakultas Hukum Untan (Jurnal Mahasiswa S1 Fakultas Hukum) Universitas Tanjungpura, 2017)
The Undergraduate Thesis that writer write is : â€œFUN SHOP Responsibility On Guarantee Agreement For Buyer On Buy And Sell Laptop Agreement In Pontianak Cityâ€ And the formulation problem on this Undergraduate Thesis isÂ  : â€œIsÂ  FUN SHOP Owner Already done the Guarantee AgreementÂ  On Buy And Sell Laptop Agreement In Pontianak City?â€ The Method on this research are with Empirical method and with Descriptive Analysis approach. About the Agreement betweenÂ  FUN SHOP owner and buyer, is a buy and sell agreement just like on 1457 Burgerlijk wetbook clause, that is: Jual beli adalah suatu perjanjian, dengan mana pihak yang satu mengikatkan dirinya untuk menyerahkan suatu kebendaan, dan pihak yang lain untuk membayar harga yang telah dijanjikan. The buy and sell laptop agreement formÂ  between FUN SHOP owner and buyer are doing with unwritten agreement. In laptop guarantee agreement FUN SHOP owner and buyerÂ  are contain with the parties right and obligation. The obligation that buyer must do isÂ  the right for the FUN SHOP owner, so as for the buyer. One ofÂ  the obligation that must to fulfillÂ  for the FUN SHOP owner is repair the laptop damage that buyer have. But the Fun Shop ownerÂ  didnâ€™t do their obligation on buyer claim especially on laptop damage that buyer buy from FUN SHOP FUN SHOP owner factor that make they didnâ€™t do their obligation on Laptop damage claim is because that damage is from factory and shop owner negligence and then FUN SHOP donâ€™t have a mechanics to repair the laptop damage that buyer buy. Law effect to FUN SHOP owner thatÂ  negligence on their obligation is must repair the laptop damage that buyer buy and also can provide compensation to the buyer As for efforts that buyer can do when face this condition is doing a deliberation with Pontianak FUN SHOP owner and also can demanding compensation to the Pontianak FUN SHOP owner on laptop damage claim that buyer buy. The problem that appear from the agreement didnâ€™t doing well is just solved by Â deliberation with Pontianak FUN SHOP owner or just Â demanding compensation to the Pontianak FUN SHOP owner. Therefore , yet one of the parties to take legal actions to be sued civilly to the District Court. Keywords : Guarantee Agreement, Buy and Sell,Â  Breach